UJI AKTIVITAS DAN FORMULASI SEDIAAN LIQUID BODY WASH DARI EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea L) SEBAGAI ANTIBAKTERI Staphylococcus epidermidis - Fernanda Desmak Pertiwi; Firman Rezaldi; Ranny Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2022)
Telang flower (Clitoria ternatea L.) is a plant that has long been used in medicine and has been shown to have antibacterial activity. This study aims to determine and test the antibacterial activity against S. epidermidis bacteria. This research method uses laboratory experiments conducted in vitro. The liquid body wash formulation of C. ternatea L. flower ethanol extract was made with various concentrations, namely 10%, 15% and 20%. The liquid body wash preparation was tested for its antibacterial activity against S. epidermidis bacteria using the disc diffusion method. The working procedure includes extraction, preparation of liquid body wash preparations, evaluation of preparations and testing of antibacterial activity of liquid body wash preparations of C. ternatea L flower ethanol extract. The results showed that C. ternatea L. flower ethanol extract had inhibitory zone activity against S. epidermidis bacteria. at each concentration, namely 10% of 3.33 mm, 15% of 3.8 mm and 20% of 6.13 mm. Meanwhile, the results of the evaluation of the preparations of all liquid body wash formulations of C. ternatea L. flower ethanol extract met the standards.